Effect of municipal solid waste compost on yield and quality of eggplant - Shabani, Hadi; Peyvast, Gholam-Ali; Olfati, Jamal-Ali; Kharrazi, Parvin Ramezani (Comunicata Scientiae, 2011)
Organic agriculture aspires to return to more closed cycles of energy and materials, maximize re-use, employ rotation systems, use nutrients of organic origin and renewable energy sources, etc. Production of municipal solid waste compost, including organic waste is increasing while soils are progressively losing organic matter due to intensive cultivation and climatic conditions. This makes the recycling of organic waste as soil amendments a useful alternative to incineration, landfill or rubbish dumps. In this study that carry out in the summer of 2008, four levels of municipal solid waste compost (50, 100, 150 and 200 t. ha-1) with control had applied. Through measured factors, marketable yield per m2, number of weed per plot, soil born disease reduction, number of leaf per plant, lateral branch rate, plants height had significant effect in 0.05 levels. The best of yield achieved of 50 t. ha-1 fertilizer level. Municipal solid waste compost also had significant effect on Ca root, fruit, leaf and root P and leaf Mg.